Thermodynamic Analysis of Hydrogen Production from Hydrogen Sulfide in Geothermal Power Plant by using Fe-Cl Hybrid Indirect Electrolysis - Fadhilla, Putri; Udi Harmoko; Marcelinus Christwardana (Universitas Muhammadiyah Sidoarjo, 2023)
Clean and sustainable energy sources are needed to meet global energy demand. Geothermal Power Plants (GPPs) may generate power from Earth's heat. However, GPPs release hazardous hydrogen sulfide (H2S) gas. To overcome this problem and maximize on resource potential, researchers have investigated converting GPP-emitted H2S into hydrogen (H2). The Fe-Cl hybrid indirect electrolysis technique is used to analyze the thermodynamics of hydrogen synthesis from H2S in GPPs. Electrolysis electricity, hydrogen generation rate, and electrolyzer energy and exergy efficiency are examined in the thermodynamic analysis. The foundation parameters show that the electrolysis process uses 20.57 kWh of power every kilogram of H2 generated. Energy and exergy efficiencies of the electrolyzer are 89.89% and 97.72%, respectively, exhibiting system efficiency. The research also examines how H2S mass flow rate and electrolysis temperature affect energy efficiency, exergy efficiency, and power consumption. Optimizing hydrogen generation and system performance requires these elements. This study analyzes the thermodynamics of hydrogen synthesis from H2S in GPPs to create sustainable and ecologically friendly energy options. H2S emissions from GPPs might be used to efficiently produce hydrogen as a renewable energy source with more research.